Infrared nano-imaging and -spectroscopy of N graphene layers on SiO2 and hexagonal boron nitride substrates - Ingrid David Barcelos (2017)
The optical response of exfoliated graphene on different surfaces (silicon dioxide (SiO2) and hexagonal boron nitride (hBN)) is investigated via scattering-type scanning near-field optical microscopy (s-SNOM) using broadband infrared synchrotron radiation. Basically, we use a commercial s-SNOM microscope integrated into the infrared synchrotron-based beamline to investigate with nanoscale resolution the optical response of different graphene layers on SiO2 or hBN substrates. Comparing atomic force microscopic topography and broadband mid-infrared images (lateral resolution of 30 nm), we confirm that optical response of both systems depends on the specific interactions between graphene and substrate as well as on the number of graphene layers. This dependence is explained by particular interactions of graphene and SiO2, wherein graphene plasmons couple to surface phonon-polaritons of SiO2. In the case of graphene and hBN, we observe coupling of the graphene plasmon to the hyperbolic phonon-polaritons of hBN.